Evaluation of Open Tomato Cultivars for Adaptation and Yield Attributes in Central Mid-hills of Nepal - Shrestha, Surendra Lal (Nepalese Horticulture, 2022)
Tomato seedlings of nine tomato cultivars with Pusa Ruby as check were transplanted on March first to second week,2018 and 2019 at Khumaltar. Crop geometry was maintained with the 60X60 cm in three replications and fertilized with 150:120:100 NPK kg + 20-ton FYM per hectare. The main objective of this study was to evaluate and select high yielding, insect pest and disease tolerant cultivars with preferred characters at open field conditions for central mid-hills. The observation was recorded on vegetative, insect pest and disease, yield attributing parametersand response of consumers & farmers. Among the tested cultivars,HRD109showed superior performance onseptoria leafspottolerant (3.5), early days to flowering (21.8), higher number of fruits per plant (121), yield (58.80 t/ha) and 2289 gm per plant, consumers (4.5) and farmers preferred(4.1), and small fruit size (32.6 g). The next superior cultivar wasHRD7 which has late blight (4.1), days to flowering (22), the higher number of fruits per cluster (7.4) and per plant (119), superior yield (54.00 t/ha) and 2158 gm per plant, consumers (4.1) and farmers preferred (4.3), small fruit size (30.3 g). These two cultivars are recommended for cultivation in the central mid-hills of Bagmati Pradesh underopen field conditions.